Four-point bending test on a middle strength rock: numerical and experimental investigations - Aria Mardalizad; Riccardo Scazzosi; Andrea Manes; Marco Giglio (Fracture and Structural Integrity)
Developing a reliable numerical modelling technique is considered as challenge for fracture assessment of the geological materials, which are much subjected to hydrostatic pressure. For this purpose, the mechanical behaviour and the fracture pattern of a middle strength rock material, called Pietra Serena sandstone, is investigated both numerically and experimentally under a Four-Point Bending (also called Flexural) testing program. For the numerical approach, an innovative method, namely FEMcoupled to-SPH, is exploited due to its capabilities in dealing with rock mechanics related issues. Two different material models, which are the Karagozian and Case Concrete (KCC) and the Extended (Linear) Drucker- Prager, are exerted to assess their capabilities. The Flexural strength and the crack initiation area are studied based on the state of the stress in various parts of the specimen in both models, and finally the results obtained from the numerical models are compared with the data obtained from the experimental tests in order to assess the capability of the modelling approach.